2016
DOI: 10.1007/s10545-016-9995-0
|View full text |Cite
|
Sign up to set email alerts
|

Household financial burden of phenylketonuria and its impact on treatment in China: a cross‐sectional study

Abstract: SummaryBackgroundPhenylketonuria (PKU) is a rare inborn disease, which, untreated, leading to severe neurobehavioral dysfunction. Considering its complexity, the management of PKU may bring a formidable economic burden to parents and caregivers. It is still unknown what the out-of-pocket expenses are for a patient with PKU in China. This paper explores the household financial burden of classical PKU and its impact on Chinese families in a quantitative manner for the first time.MethodsA non-interventional and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 16 publications
2
36
0
2
Order By: Relevance
“…She had weight loss of 5kg during the first trimester and failedto increase weight until the third trimester;(3)Financial burden of pregnancy. As we published before (Wang 2017), patients suffer a heavy financial burden in many provinces where there are no government reimbursement policies. The cost of frequent visits and examinations may deter regular follow-up (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…She had weight loss of 5kg during the first trimester and failedto increase weight until the third trimester;(3)Financial burden of pregnancy. As we published before (Wang 2017), patients suffer a heavy financial burden in many provinces where there are no government reimbursement policies. The cost of frequent visits and examinations may deter regular follow-up (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, MS/MS and some HPLC methods are affordable only to the developed countries in the world [2 -7, 13, 19]. It is not economic even for China [23].…”
Section: A Linear Trendline B Logarhitmic Trendlinementioning
confidence: 99%
“…Romania started the national program for NBS of PKU in 1999, however probably 10 % of newborns are not screened [13]. The same percentage was reported for Bulgaria and, recently, for China [23], while many countries, perhaps all African countries [24,25], do not perform NBS. Considering the incidence of PKU in various countries, a very high number of children in the world are not correctly treated (from birth), will become severely retarded, and finally will need to be all the life in the care of the family or in special institutions.…”
Section: Introductionmentioning
confidence: 96%
“…Similarly, significant changes in trends for the keywords "Tetrahydrobiopterin" for the years 2014 versus 2017 (p=0.002), 2015 versus 2017 (p<0.001), classical PKU was estimated to be 75% of the total annual family income. 31 Phenylketonuria represents one of the most prevalent autosomal recessive hereditary disorders in Turkey. 32 On the other hand, the PAH gene in Iranian Azeri Turkish population was studied, it confirmed that Variable Number of Tandem-Repeat (VNTR) alleles with thirteen repeats showed 3% frequency in the studied population.…”
Section: Concerningmentioning
confidence: 99%